The Importance of IGHV Mutational Status in del(11q) and del(17p) Chronic Lymphocytic Leukemia - Gladstone, Douglas E. (2012)
Limited outcome data exist for patients with chronic lymphocytic leukemia (CLL) with a poor-risk cytogenetic profile and a good-risk (mutated) immunoglobulin heavy-chain variable (IGHV) sequence. In a retrospective, single-institution review, 1 in 4 patients with del(11q or 17p) CLL had a mutated IGVH sequence. We found that mutational status was a better predictor for treatment intervention and OS. IGHV has prognostic value in del(11q) and del(17p) patients with CLL. BACKGROUND: Most patients with CLL with a poor-risk cytogenetic profile have an unmutated IGHV sequence. Limited clinical information exists for patients with CLL who have a poor-risk cytogenetic profile and a mutated or good-risk IGHV status. We retrospectively screened all patients with CLL seen at our institution from 2006 onward who harbored a del(11q) or del(17p) CLL detected by fluorescence in situ hybridization (FISH) analysis for whom an IGHV analysis was requested. In 66 evaluable patients, 50 (76%) had an unmutated IGHV sequence. Thirty-nine patients (59%) had del(11q) and 27 patients (41%) had del(17p); no patient in this series had both del(11q) and del(17p). The patients’ initial clinical presentations were similar in both mutational groups. Patients with an unmutated IGHV sequence were more likely to receive treatment and to have a shorter survival, with an estimated 3-year overall survival (OS) of 81% compared with 100% in the group with a mutated IGHV sequence (log rank, P = .06). These data suggest that IGHV mutational status has prognostic relevance even in patients with CLL who are defined as poor risk by genomic FISH analysis.